2012
DOI: 10.1007/s10156-011-0366-3
|View full text |Cite
|
Sign up to set email alerts
|

A case of novel swine influenza A (H1N1) pneumonia complicated with virus-associated hemophagocytic syndrome

Abstract: Influenza related to complications such as pneumonia and encephalitis have sporadically been reported. However, influenza A (H1N1)-virus-associated hemophagocytic syndrome (VAHS) has rarely been reported. A 39-year old woman complained of high fever and was referred to us. Chest infiltrations in both lungs and a positive polymerase chain reaction (PCR) for novel swine origin influenza A (H1N1) in bronchial alveolar lavage fluid (BALF) specimen was confirmed and she was diagnosed with influenza A (H1N1) pneumon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 18 publications
0
11
0
Order By: Relevance
“…Seasonal (H3N2), avian (H5N1), and swine (non-pandemic) (H1N1) influenza have all been associated with fatal cases of HPS in immunocompromised and in immunocompetent hosts [5][6][7][8][9][10][11][12][13]. It is a rare disease whose exact incidence is not known.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Seasonal (H3N2), avian (H5N1), and swine (non-pandemic) (H1N1) influenza have all been associated with fatal cases of HPS in immunocompromised and in immunocompetent hosts [5][6][7][8][9][10][11][12][13]. It is a rare disease whose exact incidence is not known.…”
Section: Discussionmentioning
confidence: 99%
“…Only English language papers were reviewed. This search revealed 15 other cases of adults with influenza A associated HPS [5][6][7][8][9][10][11][12][13] and a prospective observational study carried out in 25 critically ill patients with VAHS secondary to influenza H1N1 which was not included in the analysis because of incomplete individual patient data [14].…”
Section: Methodsmentioning
confidence: 99%
“…Although she tested negative for influenza A and influenza B antibodies, the patient tested are effective in reducing pulmonary lesions and suppressing cytokines, leading to a shutdown in macrophage activation. (6)(7)(8) It is reasonable to assume that, in the present case, erythromycin had an immunomodulatory effect rather than an antimicrobial effect when combined with a high dose of prednisolone.…”
Section: To the Editormentioning
confidence: 98%
“…It has been reported that macrolides can be effective for severe inflammation, since it is evident that they decrease neutrophil chemotaxis and infiltration into the respiratory epithelium, downregulating adhesion molecule expression and enhancing neutrophil apoptosis. (6,7) In addition, animal studies have shown that high doses of steroids …”
Section: Letter To the Editormentioning
confidence: 99%
“…The treatment, either primary or secondary, includes protocols with immunosuppressive pharmacotherapy (Etoposide, dexamethasone, cyclosporin A), 15,16 prophylactic antimicrobial therapy, and fresh frozen plasma or cryoprecipitated (if there is acute bleeding or platelet count <50×109/L) 9 , alongside an adequate evaluation of cardiac function due to the risk of myocardial injury caused by inflammation or drug toxicity.…”
Section: 12mentioning
confidence: 99%